Study of Psychiatric Morbidity of Spouse of Male Alcoholic Patients in Nepal - Sedain, CP (Journal of Chitwan Medical College, 2013)
The Problem of alcohol consuming is increasing in the world. The subjects for this study comprised of all consecutive spouses of male alcoholic patients on psychiatric department of CMC Teaching Hospital, Bharatpur, Nepal are taken as cases. This is a prospective study on the data recorded in the psychiatric department of CMC Teaching Hospital. The ratios and proportions were used for statistical analysis. The study was conducted from 1st January 2011 to 30 th December 2011.The GHQ-12 was applied and score above 2 was again examined by psychiatrist for psychiatric diagnosis ICD-10 DCR was used for diagnosis. This study shows that total number of cases ( spouses of male alcoholic patients) is 46 (100%). Depressive disorder is 13 (28.26 %) followed by conversion disorder 5 ( 10.86 %) and anxiety disorder 4 ( 8.70 %). Data shows highest number of cases were age group 30-39 (N-16, 34.78%) followed by 40-49 (N-10, 21.74%).HIghest number of cases were caste of Baisya (N-22, 47.83%) followed by Sudra (N-11, 23.91%). The current study shows that souses of male alcoholic developed depressive disorder i.e. in highest number (N-13,28.26 %) followed by conversion disorder 5 (N-5, 10.86 %) and anxiety disorder (N-4, 8.70% ) etc. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8630 Journal of Chitwan Medical College 2013; 3(3): 10-13